Study of Atonic Concentration and Types of Biostimulants Applications on Chili Pepper (Capsicum frutescens L.) Production - Jhon Hardy Purba; Negussie Siyum (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
The study aims to determine the level of atonic concentration and the type of biostimulant that can increase the yield of small chili peppers in the lowlands. The design used was a factorial Randomized Block Design (RBD) consisting of two factors. The first factor is the concentration of atonic (A), namely: A0 = 0.0 ml / l; A1 = 1.5 ml / l, A2 = 2 ml / l; and A3 = 2.5 ml / l. The second factor is the provision of several types of biostimulants (B), namely: B0 = without biostimulant; B1 = Plant Growth Stimulator; B2 = EM4; B3 = Superbionic Fertilizer. Data analysis used analysis of variance and if there was significance, further testing was carried out with the Duncan Multiple Range Test. The results showed that the urea fertilizer package with a dose of 200 kg / ha, SP-36 50 kg / ha, and KCl 50 kg / ha gave better seed yields than the control but was not significantly different from higher doses of N, P, K fertilizers.